Checklist of the subfamily Scolytinae (Coleoptera: Curculionidae) in Tucumán province, Argentina - Córdoba, Silvia P.; Atkinson, Thomas H.; Mendoza, Eduardo A. (Zootaxa, 2023)
A checklist of Scolytinae species is presented to contribute to the knowledge of the biodiversity of the subfamily in Tucumán province, Argentina. The inventory was based on collections in the field from 2016 to 2023, and a review of the material deposited in the entomological collections of the Museo de La Plata, the Museo Argentino de Ciencias Naturales Bernardino Rivadavia, and the Fundación Miguel Lillo. Previous bibliographic records were also included. In total, 54 species belonging to 11 tribes were recorded, of which six were new reports for Argentina and nine for Tucumán province; eight species were introduced. The genus Amasa was also recorded in Argentina for the first time.